Material Considerations in Structural Steel Design - Barsom, J.M. (Engineering Journal, 1987)
Engineering structures, with very few exceptions, perform safely and reliably. The safety and reliability of these structures has been achieved primarily by adhering to the appropriate specifications that govern the material, design, fabrication and inspection for the particular structure. These specifications undergo periodic reviews and, when necessary, are changed to improve their accuracy and applicability. Deviations from the specifications requirements, misinterpretation of specifications, the use of highly restrained complex welded details and use of new and unproven concepts in design may impair the safety and reliability of a structure. The collapse of a structure or the fracture of a structural component may occur as a result of improper material properties, design, fabrication, inspection, erection and operating conditions. This paper focuses on material considerations and presents a brief discussion of some material factors that should be understood and considered in the fabrication and design of steel structures. The effects of deoxidation practice on segregation in steel ingots, and in the final product are discussed. Also discussed are the variability in the yield and tensile strength properties within a plate or a structural shape and the effects of temperature and rate of loading on these properties. Finally, the paper discusses the variability in fracture toughness and the effects of temperature and rate of loading on this material property. Charpy V-notch test results are used to describe the variability in fracture toughness and the critical stress-intensity factor is used to describe the effects of temperature and rate of loading on fracture toughness. Correlations between CVN test results and the critical stress intensity factor are also presented.